Physical health monitoring after rapid tranquillisation: clinical practice in UK mental health services - Carol Paton; Clive E. Adams; Stephen Dye; Oriana Delgado; Chike Okocha; Thomas R. E. Barnes (SAGE Publishing, 2019)
Background: We aimed to assess the quality of physical health monitoring following rapid tranquillisation (RT) for acute behavioural disturbance in UK mental health services. Methods: The Prescribing Observatory for Mental Health (POMH-UK) initiated an audit-based quality improvement programme addressing the pharmacological treatment of acute behavioural disturbance in mental health services in the UK. Results: Data relating to a total of 2454 episodes of RT were submitted by 66 mental health services. Post-RT physical health monitoring did not reach the minimum recommended level in 1933 (79%) episodes. Patients were more likely to be monitored (OR 1.78, 95% CI 1.39-2.29, p  < 0.001) if there was actual or threatened self-harm, and less likely to be monitored if the episode occurred in the evening (OR 0.79, 95% CI 0.62-1.0, p  < 0.001) or overnight (OR 0.57, 95% CI 0.44-0.75, p  < 0.001). Risk factors such as recent substance use, RT resulting in the patient falling asleep, or receiving high-dose antipsychotic medication on the day of the episode, did not predict whether or not the minimum recommended level of post-RT monitoring was documented. Conclusions: The minimum recommended level of physical health monitoring was reported for only one in five RT episodes. The findings also suggest a lack of targeting of at-risk patients for post-RT monitoring. Possible explanations are that clinicians consider such monitoring too demanding to implement in routine clinical practice or not appropriate in every clinical situation. For example, physical health measures requiring direct contact with a patient may be difficult to undertake, or counter-productive, if RT has failed. These findings prompt speculation that post-RT monitoring practice would be improved by the implementation of guidance that integrated and refined the currently separate systems for undertaking and recording physical health observations post-RT, determining nursing observation schedules and detecting acute deterioration in physical health. The effectiveness and clinical utility of such an approach would be worth testing.